2017
DOI: 10.1364/oe.25.00a953
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of atmospheric NO_2 by employing the continuous-wave differential absorption lidar technique

Abstract: Differential absorption lidar (DIAL) technique employed for remote sensing has been so far based on the sophisticated narrow-band pulsed laser sources, which require intensive maintenance during operation. In this work, a continuous-wave (CW) NO DIAL system based on the Scheimpflug principle has been developed by employing a compact high-power CW multimode 450 nm laser diode as the light source. Laser emissions at the on-line and off-line wavelengths of the NO absorption spectrum are implemented by tuning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Atmospheric NO 2 has a relatively broadband absorption spectrum in the visible region around 450 nm, which provides the possibility of employing high-power multimode laser diodes for differential absorption measurements. Recently, we have developed a DIAL technique based on the Scheimpflug lidar, by introducing the tunable diode laser absorption spectroscopy (TDLAS) into the lidar fields [22]. The λ on wavelength at around 448.6 nm and the λ off wavelength at around 452.1 nm can be alternatively generated by modulating the driving current and tuning the case temperature of the high-power laser diode.…”
Section: Atmospheric No 2 Monitoringmentioning
confidence: 99%
“…Atmospheric NO 2 has a relatively broadband absorption spectrum in the visible region around 450 nm, which provides the possibility of employing high-power multimode laser diodes for differential absorption measurements. Recently, we have developed a DIAL technique based on the Scheimpflug lidar, by introducing the tunable diode laser absorption spectroscopy (TDLAS) into the lidar fields [22]. The λ on wavelength at around 448.6 nm and the λ off wavelength at around 452.1 nm can be alternatively generated by modulating the driving current and tuning the case temperature of the high-power laser diode.…”
Section: Atmospheric No 2 Monitoringmentioning
confidence: 99%
“…Briefly, the rule of Scheimpflug principles states that in a scenario where the object plane is tilted, sharp focus can be achieved by tilting the image sensor to a proper angle, where the image plane intersecting with the object plane and lens plane at the same point. Many scientific studies were benefit from it, such as particle image velocimetry [17][18][19], atmospheric aerosol monitoring [20][21][22][23][24][25][26] and fluorescence hyperspectral LIDAR [27][28][29][30]. Our previous study [31,32] has shown the potential to measure the distance profiles by light-sheet based two-dimensional Scheimpflug LIDAR, which also demonstrates the ability of large measuring range.…”
Section: Introductionmentioning
confidence: 99%
“…The Scheimpflug lidar technique has recently been developed for atmospheric aerosol monitoring, combustion diagnostics, etc. [30][31][32][33][34][35][36][37][38][39][40]. The range-resolved atmospheric backscattering signal can be retrieved by a Scheimpflug-principle based imaging system.…”
Section: Introductionmentioning
confidence: 99%